Dye sensitized solar cells: optimization of Grätzel solar cells towards plasmonic enhanced photovoltaics - Essner, Jeremy (Kansas State University, 2011)
With the worldly consumption of energy continually increasing and the main source of this energy, fossil fuels, slowly being depleted, the need for alternate sources of energy is becoming more and more pertinent. One promising approach for an alternate method of producing energy is using solar cells to convert sunlight into electrical energy through photovoltaic processes. Currently, the most widely commercialized solar cell is based on a single p-n junction with silicon. Silicon solar cells are able to obtain high efficiencies but the downfall is, in order to achieve this performance, expensive fabrication techniques and high purity materials must be employed. An encouraging cheaper alternative to silicon solar cells is the dye-sensitized solar cell (DSSC) which is based on a wide band gap semiconductor sensitized with a visible light absorbing species. While DSSCs are less expensive, their efficiencies are still quite low compared to silicon. In this thesis, Grätzel cells (DSSCs based on TiO2 NPs) were fabricated and optimized to establish a reliable standard for further improvement. Optimized single layer GSCs and double layer GSCs showing efficiencies >4% and efficiencies of ~6%, respectively, were obtained. Recently, the incorporation of metallic nanoparticles into silicon solar cells has shown improved efficiency and lowered material cost. By utilizing their plasmonic properties, incident light can be scattered, concentrated, or trapped thereby increasing the effective path length of the cell and allowing the physical thickness of the cell to be reduced. This concept can also be applied to DSSCs, which are cheaper and easier to fabricate than Si based solar cells but are limited by lower efficiency. By incorporating 20 nm diameter Au nanoparticles (Au NPs) into DSSCs at the FTO/TiO2 interface as sub wavelength antennae, average photocurrent enhancements of 14% (maximum up to ~32%) and average efficiency enhancements of 13% (maximum up to ~23% ) were achieved with well dispersed, low surface coverages of nanoparticles. However the Au nanoparticle solar cell (AuNPSC) performance is very sensitive to the surface coverage, the extent of nanoparticle aggregation, and the electrolyte employed, all of which can lead to detrimental effects (decreased performances) on the devices.
Keywords: Dye-sensitized solar cells; Au nanoparticles; Photovoltaics; Surface plasmons; Plasmonic enhancement; Protection layer; Alternative Energy (0363); Nanotechnology (0652); Sustainability (0640)